1979
DOI: 10.1149/1.2129083
|View full text |Cite
|
Sign up to set email alerts
|

The Source of Oxygen in the Anodization of Vanadium

Abstract: Single crystals of vanadium have been anodized by the method of Keil and Salomon for water soluble oxides. Oxygen-18 enriched water or acetic acid was used in order to trace the oxygen ~rom the acetic acid based solution to the oxide film. The oxygen isotope in the oxide film was determined by the method of nuclear microanalysis utilizing the i60(d,p) and isO(p,~) reactions. The results were compared to those for zirconium anodized in an isO enriched water-based solution. The results showed that, while the zir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Therefore, AOFs on transition metals can consist of different oxide phases [7,10]. In particular, the phase composition of anodic oxides on vanadium has been identified by different authors as either V 2 O 5 [4,10,11] or VO 2 [9,12,13], or as a mixture of V 2 O 5 and lower oxides [10,[14][15][16]. Also, passive films composed of barium vanadate [14] or vanadophosphate [17] can be obtained by anodization of V in aqueous solutions in some cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, AOFs on transition metals can consist of different oxide phases [7,10]. In particular, the phase composition of anodic oxides on vanadium has been identified by different authors as either V 2 O 5 [4,10,11] or VO 2 [9,12,13], or as a mixture of V 2 O 5 and lower oxides [10,[14][15][16]. Also, passive films composed of barium vanadate [14] or vanadophosphate [17] can be obtained by anodization of V in aqueous solutions in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…When vanadium is anodized in an aqueous solution, the vanadium oxide film tends to dissolve in the solution as vanadyl ions [12,14,18]. Therefore, because of the solubility of vanadium oxides in water, non-aqueous solutions are necessary for obtaining uniform oxide films on vanadium by anodization.…”
Section: Introductionmentioning
confidence: 99%
“…Keil and Salomon (3,4) grew the first anodic oxide films on vanadium using an acetic acid electrolyte containing a small quantity of water and saturated with sodium tetraborate, and concluded that the films were composed of V204. The same electrolyte was used by Mackintosh and Plattner (5) in a transport number study which identified the oxide as V205, and by Lewis and Perkins (6) who concluded that the tetraborate, not the water, acted as the source of oxygen for the film. Pelleg (7) found an acetone-based electrolyte (again containing sodium tetraborate) in which anodic oxide films could be grown,.but his interest was in microsectioning vanadium, not in growing oxide.…”
mentioning
confidence: 99%
“…Owning to vanadium oxide film tends to dissolve as vanadyl ions in the aqueous solution during anodizing process ( Yang et al., 2011 ). To induce the porous structure, the Na 2 B 4 O 7 as extra oxygen source is introduced in the solution ( Lewis and Perkins, 1979 ). The nanoporous (NPs) V 2 O 5 electrodes were prepared by anodizing process.…”
Section: Resultsmentioning
confidence: 99%